FACTORS RELATED TO FIRST ANTENATAL VISITS IN PREGNANT WOMEN - Maria Bernadeta S Djano; Muhammad Ardian Cahya Laksana; Budi Utomo (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: Pregnancy is a physiological event but in its developmen it has risks. In Nagekeo district in 2018 and 2019 there were 6 cases of maternal death and 121 cases of infant mortality with 52 deaths occurring antepartum. There were 10 infant deaths at the Boawae Health Center in 2019 with 5 cases of death occurring antepartum. In addition, there is a gap in achieving the first antenatal visit target of 19% and 14.8% in 2018 and 2019 where not all pregnant women have had their first pregnancy examination in the first trimester. Several factors can influence the behavior of pregnant women in conducting the first antenatal visit such as education level and cost. The importance of carrying out a pregnancy check in the first trimester allows for early detection of disease, administration of folic acid, communication and health information as well as management of problems found. This study aims to analyze the factors associated with the first antenatal visit in pregnant women. Methods: This type of research is observational analytic with a cross sectional design. The sample in this study were all pregnant women in the 2nd and 3rd trimesters who were in the working area of the Boawae Health Center. Data collected through questionnaires were then processed and analyzed by frequency distribution and cross distribution as well as Multiple Logistics Regression analysis with a significance level of 5% (p = 0.05). The research sample size is 86 respondents. The sampling technique is non-probability sampling with consecutive sampling. Bivariate data analysis using chi square and multivariate test using multiple logistic regression. Results: The results showed that the factors associated with the first antenatal visit were maternal health status with a p-value of 0.001 (p < 0.005), husband's education with a p-value of 0.000 (p < 0.005), pregnancy complications with a p-value of 0.001 (p < 0.005), costs with a p-value of 0.002 (p < 0.005) and the presence of a companion with a p-value of 0.000 (p < 0.005). Multivariate analysis showed that the most dominant factor influencing was the cost and presence of a companion, so it can be concluded that pregnant women who have KIS and are supported by a companion are more likely to have their first visit in the first trimester of pregnancy. Conclusion: There is a relationship between health status, husband's education, costs, presence of companions, pregnancy complications with the first antenatal visit.